Analisa Kepuasan Pelanggan Terhadap Kualitas Pelayanan PT. CST Indonesia Melalui Model Analisis Kuantitatif "TEV" - Saparudin Saparudin; Tyas Eka Kurnia (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This paper describes the measurement of customer satisfaction for the service quality at English course company using “TEV” Quantitative Analysis Model. This study not only measures customer satisfaction from one dimension of service quality but from five dimensions of service quality. This study has analysis dimension of service quality which to be the priority for the customer from the specialist aspect. Data processing was performed with TEV Quantitative Analysis Model that is weighted with Delphi Method and the Expected Value of performance assessment. Results from this study that the assessment of customer satisfaction for service quality corporate are categorized on a scale of four with a very satisfaction value 3.28. Of the 23 indicators measured, there are 16 indicators that are categorized very satisfaction, seven indicators of satisfaction categorized, zero indicators of disappointed, and zero indicator is considered very disappointed.Keywords: TEV Quantitative Analysis, Analysis Model, Customer Satisfaction, Service Quality, Delphi